Mouse$1 (Bs first Christmass - Thompson, Lauren; Erdogan, Buket (New York : Simon & Schuster Books for Young Readers, 1999)
While exploring the house on Christmas Eve, a little mouse discovers the tree, a candy cane, a stocking, a jingle bell, and Santa Claus.
Keywords: Christmas -- Fiction; Mice -- Fiction